2008
DOI: 10.1016/j.ajog.2007.06.065
|View full text |Cite
|
Sign up to set email alerts
|

Experimental amniotic fluid infection in sheep: Effects of Ureaplasma parvum serovars 3 and 6 on preterm or term fetal sheep

Abstract: Objective-To determine effects in late gestation of U. parvum serovar 3 colonization, and effects, preterm, of U. parvum serovar 6. Study design-Ewes received an intra-amniotic (IA) injection of U. parvum serovar 6 (20x10 6 cfu; n=9), U. parvum serovar 3 (20x10 3 cfu; n=6), vehicle (n=10) or saline (n=4) on day 80 of pregnancy (d). Lambs were delivered at 125d (ureaplasma, n=9; saline or media controls, n=9) or 145d (ureaplasma, n=6; media controls, n=5) for assessment of inflammation and lung maturation.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 30 publications
4
83
1
Order By: Relevance
“…less systemic inflammation and inconsistent lung maturation (17). Intra-amniotic C. albicans causes a substantially different inflammatory response, characterized by severe inflammation in the fetal lung, inflammation and edema of the fetal skin (18), and fetal death beyond 3 d of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…less systemic inflammation and inconsistent lung maturation (17). Intra-amniotic C. albicans causes a substantially different inflammatory response, characterized by severe inflammation in the fetal lung, inflammation and edema of the fetal skin (18), and fetal death beyond 3 d of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…We previously described models of the fetal inflammatory response syndrome in sheep using the proinflammatory mediators Escherichia coli lipopolysaccharides (15), interleukin (IL)-1 (16), and live Ureaplasma parvum (17). In contrast to the low-grade fetal inflammation caused by these agonists, we recently reported that intra-amniotic C. albicans caused a severe, progressive fetal inflammation within 2 d, with the severity of skin, lung inflammatory, and systemic responses threatening fetal viability (18).…”
mentioning
confidence: 99%
“…This ureaplasma colonization model in fetal sheep replicates the chronic and indolent human fetal exposure to ureaplasmas that can result in preterm birth (14) or may be tolerated by the pregnancy without overt pathology (15). As in the human, fetal sheep colonized with ureaplasmas can have induced lung maturation and indicators of chronic lung inflammation (16). Acute ureaplasma infection of fetal baboons seemed to increase lung injury with chronic ventilation at birth (17).…”
mentioning
confidence: 99%
“…Recently, in a sheep or mouse pregnant model of intrauterine infection of U. parvum, it was found that U. parvum could not be recovered from lung tissues 2-3 days after birth in term pups. 9,10 Therefore, in human term newborns, U. parvum may not be able to be recovered from lung tissues. This observation is consistent with previous studies in the sheep model showing clearance of Ureaplasma from the nasal cavities soon after birth 11 and an inability of Ureaplasma to colonize the respiratory tract of older lambs.…”
Section: Discussionmentioning
confidence: 99%